Optimasi Penjadwalan Mesin dan Shift Karyawan Menggunakan Algoritme Genetika (Studi Kasus Pada PT. Petro Jordan Abadi) - Sarah Aditya Darmawan; Imam Cholisoddin; Tibyani Tibyani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Employee shift scheduling and machine scheduling are two things to keep in mind at a factory. Employee shift scheduling is needed to manage employees' working hours so that the work quality of employees is well maintained and has a positive impact on the company. So it is with machine scheduling. Machine scheduling is needed to regulate the order and process of machine work in goods production activities, in order to shorten production time of goods and increase production of goods. The crossover method used is one-cut point crossover, mutation method used for shift scheduling is reciprocal exchange mutation and insertion mutation for machine scheduling, and selection method used is elitism selection. There are 4 scheduling systems used in this study, testing the value of popsize, testing the value of generation, convergence testing, testing the combination of cr and mr values, and testing of global analysis. In testing the value of popsize obtained the highest popsize is 70 with a fitness value of 0.6198. The generation value test got the highest generation in generation 400 with fitness value 0,5624. As for testing cr and mr get the best value at cr of 1 and mr of 0 with a fitness value of 0.5926. Results obtained from global analysis is the fitness value of the system has a higher yield of 0.5162. It can be concluded that the application of genetic algorithms in the optimization of machine scheduling and shift employees is very influential in the process of obtaining the best solution. The greater the fitness value obtained the better the solution obtained, and vice versa. So that the engine optimization system and employee shift scheduling can be used as a reference for the schedule for the company.